Ecological Restoration of Southwestern Ponderosa Pine Forests (The Science and Practice of Ecological Restoration Series) (Island Press, 2003)
Ecological Restoration of Southwestern Ponderosa Pine Forests brings together practitioners and thinkers from a variety of fields—including forestry, biology, philosophy, ecology, political science, archaeology, botany, and geography—to synthesize what is known about ecological restoration in ponderosa pine forests and to consider the factors involved in developing and implementing a successful restoration effort. The book examines: